Modelling food security and agricultural diversification prospects in Vietnam - Dao, Thê Tuân; Le, Thi Châo Dung (Cahiers Agricultures, 1996)
Food production bas increased in Vietnam, but food security per capita remains uncertain. The present modelling study was aimed at simulating fluctuations in various objectives (urban and rural industrialization, urban population growth, food security and agricultural diversification projects), for three future dates (2000, 2005 and 2010). 45 interrelated variables were monitored, e.g. urbanization, income, yield, increased meat consumption at the expense of cereals, and arable land/farm. Typical constraints encountered under Vietnamese conditions were taken into account in the simulations (pressures on the land, activity rate in the farming sector, and food demand modifications). The projections varied in relation to the chosen GDP rate of growth and the extent of industrialization. There were no observed inconsistencies between food security and agricultural diversification, and it is estimated that future needs can be met.